External egg morphology of two parthenogenetic species of the genus Dahlica Enderlein (Lepidoptera: Psychidae) - Lovtsova, Julia A.; Kochiev, Mikhail V.; Kolesnichenko, Kirill A. (Zootaxa, 2022)
The egg chorion morphologies of Dahlica triquetrella (Hübner, 1813) and Dahlica lichenella (Linnaeus, 1761) are described. These two species well differ from each other by diameter of the micropyle, by number of micropyle pores, and by diameter of the micropyle rosette.